A promising new tool for literacy instruction: The morphological matrix - Ng, Melvin M. R.; Bowers, Peter N.; Bowers, Jeffrey S. (PLOS ONE, 2022)
There is growing interest in the role that morphological knowledge plays in literacy acquisition, but there is no research directly comparing the efficacy of different forms of morphological instruction. Here we compare two methods of teaching English morphology in the context of a memory experiment when words were organized by affix during study (e.g., a list of words was presented that all share an affix, such as <doing>, <going>, <talking>, <walking>, etc.) or by base during study (e.g., a list of words was presented that all share a base, such as <doing>, <done>, <redo>, <undo>). We show that memory for morphologically complex words is better in both conditions compared to a control condition that does not highlight the morphological composition of words, and most importantly, show that studying words in a base-centric format improves memory further still. We argue that the morphological matrix that organizes words around a common base may provide an important new tool for literacy instruction.